(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Introduction: Age-related cataract is the leading cause of blindness in the world. (AP)-endonuclease APE1 and the X-ray cross-complementing group 1 (XRCC1) are the key enzymes taking part in the repair of DNA damage. The association of X-ray cross-complementing group 1 (XRCC1) and AP endonuclease-1 (APE1) plays a critical role as polymorphisms of DNA repair genes decreasing the ability to repair DNA damage, leaving human body a greatly increased susceptibility to cancer or age-related diseases. Aim and objective: To study the Molecular characterization and its Association to AP endonuclease-1 (APE) and X-ray cross-complementing group 1 (XRCC1), as a DNA Repair protein from patients with the risk of age-related cataract at a Tertiary Care Centre, Uttar Pradesh. Material and methods: This was a case control study carried out in the Department of Anatomy & Department of Ophthalmology of RMCH&RC for a period of 2 year i.e., June 2020 to June 2022. A total of 500 clinical suspected cases were included in our study in which 250 patients were confirmed as cataract positive patients whereas 250 were the Controls. The Demographic profiles of the cases were recorded after duly obtaining consent. The 5ml of venous blood was collected in Ethylene diamine tetraacetic acid tubes. DNA was extracted by using Qiagen DNA Extraction kit as per manufactures guidelines. The AP endonuclease-1 (APE) and X-ray cross-complementing group 1 (XRCC1) gene was detected by the conventional PCR. Results: In the present study the maximum number of cases were reported in the Females as compared to the Males with the maximum age group of 51-60 years being affected the most. The Expression of (AP) –endonuclease (APE1) gene was more 68.4 % as compared to X-ray cross-complementing group 1 (XRCC1) with 62.8 %. The increase expression indicates the presence of these genes in the DNA repair damage. Conclusion: The Expression of (AP)-endonuclease (APE1) gene was more 68.4% as compared to X-ray cross-complementing group 1 (XRCC1) with 62.8%. The increase expression indicates the presence of these genes in the DNA repair damage. So, there should be early screening and its molecular detection of the DNA repair gene, which will help the clinician in the early diagnosis as well as early treatment of the cataract.